2012
DOI: 10.7182/pit2012579
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Alterations in Body Image Imposed by the Left Ventricular Assist Device: A Case Report

Abstract: Little is known about clothing issues among patients with implantable left ventricular assist devices (LVADs). This article describes the experience of a woman who had challenges in adapting to an altered body image imposed by the external components of the LVAD system. The woman discusses her problems about clothes that fit her personal style and shares her strategies and recommendations in overcoming the problem. Her description of how she approached and resolved the problem is situated within the Apparel Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…), and 3) social isolation because of such limitations and altered body image. [9][10][11]27 The current study extends the previous literature examining the effect of body image on personal wellbeing among LVAD implanted patients. Other studies have found that LVAD implanted patients modified their own self-image, among others, by choosing clothes hiding the LVAD, an action that helped them improve their QOL.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…), and 3) social isolation because of such limitations and altered body image. [9][10][11]27 The current study extends the previous literature examining the effect of body image on personal wellbeing among LVAD implanted patients. Other studies have found that LVAD implanted patients modified their own self-image, among others, by choosing clothes hiding the LVAD, an action that helped them improve their QOL.…”
Section: Discussionsupporting
confidence: 72%
“…5 Similarly, external components of the LVAD system were found to cause LVAD implanted patients dissatisfaction with their own body image, which led patient to look for strategies to overcome this problem. 10 Strategies included wearing clothes that did not accentuate the LVAD on one hand and that preserved and expressed the patient's personal style, on the other. Therefore, the first purpose of the current study was to investigate whether there is a relationship between body image and personal wellbeing among LVAD implanted patients.…”
Section: Introductionmentioning
confidence: 99%
“…Even with the introduction of smaller, durable MCS, body image issues may be more prevalent in women and could influence their decision to pursue MCS. (33)…”
Section: Sex Differences In Utilization Of Mcsmentioning
confidence: 99%
“…68 Emotional distress, adjustment disorders, and disability have been identified after device implant. 9,10 …”
Section: Coping and Adaptation In Lvad Patients: A Meta-synthesismentioning
confidence: 99%